Development of Nanotechnology for Manned and unmanned Aircraft: Perspectives on Jet Engines, Fuels, spacecraft, AI, and Sustainability (London Journal of Engineering Research, 2025)
These days, nanotechnology has provided an enormous benefit to the aviation and aerospace industries for improved manufacturing, spacecraft, fuels, health, and more. The objective of this paper is to review and propose a higher level of nanotechnology development in the aviation industry. While space exploration and tourism have brought about an appreciation for Earth's environmental changes from space, numerous criticisms have indicated the large negative impact space travel has made on the environment. Here,nanotechnology is offered as a field that can both improve space tourism and decrease its impact on the Earths environment. Specifically, this paper starts with a review of what material properties are needed for space exploration and then suggests the use of nanotechnology in the development of improved composite materials for jet engines, propulsion, and durability, considering aeronautical standards and aerospace developments, introducing the implementation of artificial intelligence (AI). This research includes aerospace and aeronautical industrymanufacturers, their new nanotechnological strategies and breakthroughs, as well as failed attempts during manufacturing or operations. Addressing the failures, this research indicates possible future steps for developing nanotechnology in unmanned and manned aircraft to reduce harm to the environment while still achieving space exploration.
Keywords: Carbon nanotubes (CNTs); Functionalization of CNTs; Chirality; Arc discharge; laser ablation; Biosensors.; manufacturing.; industry; Technological tasks; metalworking; visualization of the axiom control CNC system